2017
DOI: 10.1371/journal.pone.0182789
|View full text |Cite|
|
Sign up to set email alerts
|

Methyl pyruvate protects a normal lung fibroblast cell line from irinotecan-induced cell death: Potential use as adjunctive to chemotherapy

Abstract: The Warburg Effect, characterized by increased rate of glycolysis even under normoxic conditions, is one of the hallmarks of cancer. Relatively lower oxidative phosphorylation (OXPHOS) is also a characteristic feature in cancer cells. We hypothesized that interference with this phenomenon, by introducing exogenous pyruvate, would upset this cancer phenotype and boost the energy requirements of normal cells. We find that methyl pyruvate protects irinotecan-treated normal lung fibroblast cell line (MRC-5) probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
9
1
Order By: Relevance
“…We have previously shown that exogenous pyruvate kills breast, lung and ovarian cancer cell lines but promotes the survival of a normal fibroblast cell line. Furthermore, exogenous pyruvate protects the normal cell line from genotoxic stress caused by irinotecan [5]. Since monocytes are often exposed to stress caused by infectious agents, we investigated the response of THP-1 cells to LPS in order to understand the effect of superimposing infection on a cancerous monocyte.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that exogenous pyruvate kills breast, lung and ovarian cancer cell lines but promotes the survival of a normal fibroblast cell line. Furthermore, exogenous pyruvate protects the normal cell line from genotoxic stress caused by irinotecan [5]. Since monocytes are often exposed to stress caused by infectious agents, we investigated the response of THP-1 cells to LPS in order to understand the effect of superimposing infection on a cancerous monocyte.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that the reversal of the Warburg Effect in some cancer cell lines by the introduction of exogenous pyruvate is sufficient to kill them. In contrast, this strategy promotes survival in a normal cell line even when exogenous pyruvate is combined with a genotoxic agent suggesting that exogenous pyruvate can be used as an adjunctive to protect normal cells during chemotherapy [5].…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether energy stress could be a possible mechanism of cell death, flow cytometry with DRAQ7 labelling was carried out with samples treated for 48 h with either DMSO, or nelfinavir and mefloquine combination in the presence or absence of methyl pyruvate ( Figure 5 D). Methyl pyruvate can alleviate energy stress when supplemented to cells, as it is a direct substrate of the citric acid cycle to produce energy by oxidative phosphorylation [ 26 ]. Methyl pyruvate partially rescued nelfinavir and mefloquine induced cell death when supplemented to the Tsc2 −/− MEFs (causing a 40% rescue of cell death).…”
Section: Resultsmentioning
confidence: 99%
“…For example, NaPy has been shown to minimise deficits following traumatic myocardial infraction in pigs and reduce cortical contusion injury and hypoxic‐ischemic damage in rat brains . In addition, NaPy has improved rat renal function after glycerol‐induced renal failure and has been proposed as an adjunct treatment to protect fibroblast cell lines from chemotherapy‐induced death . Physiological NaPy levels in human blood are low, 0.090 to 0.12 mM, and abnormal levels of NaPy in blood serum and extracellular spaces are often an indicator of disease .…”
Section: Introductionmentioning
confidence: 99%